Neurophysiological changes associated with olfactory short-term habituation in Drosophilia melanogaster - Twick, Isabell (Trinity College (Dublin, Ireland). Department of Genetics, 2016)
The term habituation describes a simple form of learning that is characterized by a behavioural response decrement following repeated or prolonged sensory stimulation (Christoffersen, 1997; Rankin et al, 2009; Thompson and Spencer, 1966; Thompson, 2009; Ramaswami, 2014). It constitutes a filtering mechanism for sensory stimuli that filters irrelevant sensory information and only allows salient and important stimuli, such as those that predict food sources or allude death, to be passed through to higher brain centres (Wilson and Linster, 2008; Rankin et al, 2009). Filtering of innocuous sensory information is thought to be a building block for higher cognitive tasks (Wilson and Linster, 2008). In the fruit fly Drosophila melanogasler, a form of olfactory habituation has been extensively characterized behaviourally and some of the underlying neuronal mechanisms have been deciphered (Das et al., 2011b). Habituation of the olfactory avoidance response is based on a fly's innate repulsion to an aversive odourant which declines following continuous exposure to the odour (Das et al., 2011b). This form of olfactory habituation has been proposed to arise from enhanced inhibitory transmission from local interneurons onto odourresponsive projection neurons in the antennal lobe, the fly's primary processing centre for olfactory information (Das et al., 2011b).
Keywords: Genetics & Microbiology, Ph.D.; PhD Trinity College Dublin, 2016